Sharing the benefits of biodiversity the Kani TBGRI deal in Kerala, India - R. V. Anuradha (Journal of International Wildlife Law & Policy,3:2,125 - 151, 2000)
The United Nations Convention on Biological Diversity (CBD) concluded at the Earth Summit in 1992, mandates that where utilisation of the knowledge, innovations and practices of local and indigenous communities leads to benefits, such benefits shall be equitably shared with the holders of such knowledge, innovations and practices. The study analyses some of the issues that have emerged in the context of a 'benefit sharing exercise' attempted by the Tropical Botanic Garden and Research Institute (TBGRI), a research institute based in Kerala, with the Kani tribals of Kerala, pursuant to the development of a pharmaceutical drug, based on the knowledge, information and natural resources that the Kanis have nurtured over many years. As the case study illustrates, the debate on benefit sharing in the absence of other fundamental rights such as the rights to land, access to the resource and adequate governance structures becomes a limited and myopic exercise. A 'fair and equitable benefit sharing mechanism' would therefore call for certain basic pre-conditions diat will be discussed in the course of the study.